Lack of Drug‐Drug Interaction Between Filgotinib, a Selective JAK1 Inhibitor, and Oral Hormonal Contraceptives Levonorgestrel/Ethinyl Estradiol in Healthy Volunteers. Issue 4 (28th September 2020) - Begley, Rebecca; Anderson, Kacey; Watkins, Timothy R.; Weng, Winnie; Ampaw, Lorraine; Qin, Ann; Kearney, Brian P.; Mathias, Anita
Abstract: Filgotinib (FIL) is a potent and selective JAK1 inhibitor in clinical development for treatment of severe inflammatory diseases. A drug‐drug interaction study to evaluate the potential effect of FIL on the pharmacokinetics (PK) of the oral contraceptive levonorgestrel (LEVO)/ethinyl estradiol (EE) was conducted. This was a phase 1, open‐label, randomized, crossover study in healthy female subjects (N = 24). Subjects received a single dose of LEVO (150 μg)/EE (30 μg) alone (reference), or in combination with multiple‐dose FIL (200 mg once daily for 15 days; test). Intensive PK sampling was conducted, and safety was assessed throughout the study. PK interactions were evaluated using 90% confidence intervals of the geometric least squares mean ratios of the test versus reference treatments. All 24 subjects enrolled completed study treatments. Coadministration of FIL with the oral contraceptive did not alter the PK of LEVO and EE; the 90% confidence intervals of the geometric least squares mean ratios were contained within bioequivalence bounds (80%‐125%). Exposures of FIL were consistent with observed clinical exposure data. Study treatments were generally well tolerated. All adverse events were mild. Coadministration with FIL did not alter the PK of LEVO/EE, and hormonal contraceptives can serve as an effective contraception method for subjects on FIL treatment.